Treatment Of Acute Protruded Disc with Percutaneous Disc DecompressionAnd Transforaminal Epidural Steroid injection - Abood Alsamarria, Ammar Najim (Diyala Journal of Medicine, 2018)
Background: The primary goal to the surgical cureof theLower-back and radicular pain is common presenting complain of herniate lumber disc and compression of the nerve root by protrusion of disc material. Objective: To assess the effectiveness of epidural steroid injuction for low back pain in a compination with percutenous disc decompression in patients presenting to Baqubah Teaching Hospital in Diyala provenice, Iraq whom suffering from protruded disc with radicular pain. Patients and Methods: Depending on inclusion and exclusion criteria, fifty consecutive patients diagnosed as having protruded disc and whom used conservative therapy for six weeks with no improvement all were conducted in the Orthopaedic clinic in Baqubah city during 2013 till 2015, 25 patients use both method and 25 patients use only Decompressor. Results: The result were shown no significant differences between decompression and decompression+ESI for the age, sex, operating time, hospitalization, and stight leg rising test(S.L.R.T) but significant difference between decompression and decompression+ESI at p < 0.05 for time retain to work /day, numbness, and radition/pain with mean ± SD; (20.8 ± 7.4 and 15.8 ± 6.6 for time retain to work respectively), (1.3 ± 0.5 and 1.6 ± 0.5 for numbness respectively), (1.4 ± 0.5 and 1.8 ± 0.4 for radition/pain respectively). And the result revealed that the operating time was significant positive correlation with age and significant negative correlation with numbness and time retain to work/day significant negative correlation with numbness and radition/pain, while significant positive correlation with S.L.R.T, the data was taken depending on oswestry disability index (ODI) questioners. Conclusion: Used of both decompressor with epidural injection areprovided rapid relief of sciatica and low-back pain in the first three months after operation that improved the movement and early exercise.